Hydrogen electrolyser for sustainable energy production: A bibliometric analysis and future directions. (12th February 2023) - Arsad, A.Z.; Hannan, M.A.; Al-Shetwi, Ali Q.; Hossain, M.J.; Begum, R.A.; Ker, Pin Jern; Salehi, F.; Muttaqi, K.M.
Abstract: Sustainable energy demand drives innovation in energy production. Electrolysis of water can produce carbon-free hydrogen from renewable sources. This paper presents a bibliometric analysis of recent and highly referenced research on hydrogen electrolysers utilising the Scopus database to shed insight into future trends and applications. It has been discovered that the most frequently published type of study for top-ranked papers is the formulation of problems and simulations (38.3%), followed by a study of the state-of-the-art technology assessment (32.5%), laboratory research, design, and performance evaluation (24.2%), and reviews (5%). In general, 33.33% of articles focused on controlling hydrogen electrolyser efficiency. This study used different case studies from the global literature to conduct a complete evaluation of the electrolyser statistical analysis of the present state of the art, models or modes of operation, key challenges, outstanding issues, and future research. This evaluation will aid researchers in building a commercially successful hydrogen electrolyser. Highlights: A comprehensive review on hydrogen electrolyser is analysed for future research directions. The problems, state-of-the-art technology, design, and performance evaluation is reviewed. The control strategies are significantly boost the efficiency of hydrogen electrolysers. A statistical analysis on electrolyser models, open issues, and future research trend is investigated. This review will contribute to improve the efficiency and sustainability of electrolyser technology.